2010
DOI: 10.1308/003588410x12518836438840
|View full text |Cite
|
Sign up to set email alerts
|

Conservatively treated massive prolapsed discs: a 7-year follow-up

Abstract: A massive disc herniation can pursue a favourable clinical course. If early progress is shown, the long-term prognosis is very good and even massive disc herniations can be treated conservatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
55
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(62 citation statements)
references
References 37 publications
4
55
0
3
Order By: Relevance
“…Interestingly, large herniations had a greater tendency to decrease in size than small herniations in that study. 9 Other investigators 13 performed MRI for 37 humans with large prolapsed lumbar intervertebral disks who were treated conservatively. All analyzed prolapsed intervertebral disks had a reduction in volume during the study 13 ; 87% had a ≥ 50% reduction in volume.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, large herniations had a greater tendency to decrease in size than small herniations in that study. 9 Other investigators 13 performed MRI for 37 humans with large prolapsed lumbar intervertebral disks who were treated conservatively. All analyzed prolapsed intervertebral disks had a reduction in volume during the study 13 ; 87% had a ≥ 50% reduction in volume.…”
Section: Discussionmentioning
confidence: 99%
“…There is no correlation between the clinical findings and the size of the hernia [1]. Moreover, there is not yet a consensus on which method of treatment should be chosen in which stage of lumbar disc herniation (LDH) [2,3]. In recent years, because MRI scanners have become easily accessible, it may sometimes be decided to proceed with surgery according to the size of the disc herniation, ignoring the patient's clinical status [2,3].…”
Section: To the Editormentioning
confidence: 99%
“…Moreover, there is not yet a consensus on which method of treatment should be chosen in which stage of lumbar disc herniation (LDH) [2,3]. In recent years, because MRI scanners have become easily accessible, it may sometimes be decided to proceed with surgery according to the size of the disc herniation, ignoring the patient's clinical status [2,3]. However, better regression resultimg from conservative management of large disc herniation has been reported [3].…”
Section: To the Editormentioning
confidence: 99%
See 1 more Smart Citation
“…These results are similar to the recent studies done using MRI; Cribb et al 15) reported that, by following up on 15 cases with more than 50% spinal canal encroachments for 24 months, in 14 of the 15 cases, improvement of clinical symptoms was shown without surgery, and reported that on average 80% reduction in size was shown, hence suggested that a careful consideration needs to be given regarding surgery due to potential surgical complications. In addition, Benson et al 16) by following up on 37 cases with more than 50% spinal canal encroachments for 23 months, reported that 83% satisfactory results were obtained, while only 4 cases required surgery. As such, regardless of the size of herniated discs, whether to undergo a surgery needs to be decided upon consideration of the duration and progress of the symptoms, and conservative treatment needs to be undertaken first before surgery.…”
Section: ) Agementioning
confidence: 99%